2020
DOI: 10.1186/s12893-020-00793-w
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of allograft bone using titanium mesh in the posterior-only surgical treatment of thoracic and thoracolumbar spinal tuberculosis

Abstract: Background: The bony fusion of allograft bone using titanium mesh in the posterior-only surgical treatment of thoracic and thoracolumbar spinal tuberculosis has not been explained in detail. We aimed to analyze the efficacy of bony fusion of allograft bone using titanium mesh in the posterior-only surgical treatment of thoracic and thoracolumbar spinal tuberculosis. Methods: We treated 32 thoracic or thoracolumbar tuberculosis patients by one-stage posterior debridement, allograft bone graft using titanium mes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Wang B et al [13] reported 32 cases of thoracic spinal tuberculosis surgically treated using the simple posterior approach to perform focal debridement combined with titanium mesh and allograft bone graft fusion. Satisfactory clinical outcomes and good correction of the posterior convexity deformity were achieved in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wang B et al [13] reported 32 cases of thoracic spinal tuberculosis surgically treated using the simple posterior approach to perform focal debridement combined with titanium mesh and allograft bone graft fusion. Satisfactory clinical outcomes and good correction of the posterior convexity deformity were achieved in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…This preference can be attributed primarily to the limitations of drug therapy, which often struggles to achieve effective medication concentration in the lesion area without causing adverse effects on other organs [ 35 , 36 ]. Studies have shown that titanium mesh grafting has better biocompatibility and can rapidly stabilize the affected segments without causing pathology at the grafting site, making it widely used in the clinical treatment of spinal tuberculosis [ 9 , 16 , 37 ]. Meanwhile, simple bone grafting has its limitations, such as limited autologous bone quantity and potential complications from donor site bleeding and potential complications in the graft area [ 38 ]; allografts are associated with complications such as delayed healing and infection [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spinal tuberculosis surgery, allografts can potentially replace autografts. Previous studies have indicated that titanium mesh offers superior anterior column support and has a lower rate of kyphotic angle loss, especially beneficial for patients with osteoporosis and inferior iliac bone quality [ 9 16 ]. With the advancement of biomaterials and bone tissue engineering, a variety of grafting materials are now employed in the surgical treatment of spinal tuberculosis.…”
Section: Introductionmentioning
confidence: 99%